Joint and Several Liability sebagai Bentuk Mitigasi Risiko pada Bank Wakaf Mikro di Era Pandemi Covid-19 - Djawahir, Abdillah U.; Zahroh, Aisi Kholilatul (Proceedings of Annual Conference for Muslim Scholars, 2022)
The Covid-19 pandemic has harmed the global economy, Indonesia and Islamic microfinance institutions are also inseparable from the impact of the pandemic. Bank Wakaf Mikro (BWM) is a sharia microfinance institution registered and supervised by the Financial Services Authority (OJK). BWM represents financial institutions, government, and pesantren as the economic base of Indonesian Muslims. The purpose of the existence of BWM is to be able to alleviate poverty by providing financing to the productive poor through a routine assistance program whose target is the poor who cannot access formal financial institutions to assist the capital aspect of small businesses. This study aims to explore the risk of BWM financing in the Covid-19 pandemic era. By using a single case research method at BWM Sinar Sukses Bersama An-Nur II Al-Murtadlo Bululawang, Malang Regency. BWM is believed to be able to increase financial inclusion, especially for the community and Micro, Small, and Medium Enterprises (MSMEs) for easy access to capital. And it was found that Joint and Several Liability was a form of risk mitigation in the Covid-19 pandemic era. This research has implications for increasing the scientific repertoire of risk management, especially the systemic risks faced by Islamic microfinance institutions, while the managerial implications of this research are to become a reference in managing BWM to become a healthy Islamic microfinance institution. From the results of this study, it is hoped that there will be further multi-case studies or quantitative methods to confirm the results of this study.